Phenology of Flowering Time and Flowering Duration of Cucumber Plants in Padang and Kamang Magek - Pebriyeni, Silvi; Vauzia, Vauzia; Anhar, Azwir; Kardiman, Reki (Jurnal Biologi Tropis, 2025)
Cucumber (Cucumis sativus L.) is a high-value horticultural crop widely used as fresh vegetables, processed food ingredients, and cosmetic products. In addition, cucumber contains important nutrients for health, such as vitamin C, vitamin K, and various essential minerals. As a plant with many benefits, cucumber is greatly influenced by climatic conditions, which can directly affect productivity and harvest quality. Based on this, a study on the phenology of cucumber plants under two different climatic conditions was conducted. This study used an experimental method involving 20 cucumber plants, with two location treatments and two replications. The observed parameters included the time of flower emergence and flowering duration. The study was conducted from September to December 2024 at two locations, Kamang Magek and Padang. The data were analyzed using a t-test with a significance level of 5%. The results of the study showed significant phenological differences between cucumber plants grown in Kamang Magek and Padang. Plants in Kamang Magek went through generative phases earlier, marked by earlier flower emergence, which occurred on day 25.4 after planting, compared to day 29.45 in Padang. The flowering duration in Kamang Magek was also shorter, lasting 7.9 days, compared to 10.55 days in Padang. These findings indicate that differences in climatic conditions between the two locations have a significant impact on the phenological development of cucumber plants.